2002
DOI: 10.1074/jbc.m207680200
|View full text |Cite
|
Sign up to set email alerts
|

Autocatalytic Processing of γ-Glutamyltranspeptidase

Abstract: ␥-Glutamyltranspeptidase is the key enzyme in glutathione metabolism, and we previously presented evidence suggesting that it belongs to the N-terminal nucleophile hydrolase superfamily. Enzymatically active ␥-glutamyltranspeptidase, which consists of one large subunit and one small subunit, is generated from an inactive common precursor through post-translational proteolytic processing. The processing mechanism for ␥-glutamyltranspeptidase of Escherichia coli K-12 has been analyzed by means of in vitro studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
116
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(126 citation statements)
references
References 62 publications
8
116
0
Order By: Relevance
“…Interestingly, the C terminus of the L subunit and the N terminus of the S subunit are quite distant from one another with Ser-387 C and Thr-391 N being 36 Å apart. The peptide bond between Gln-390 and Thr-391 is cleaved autocatalytically by posttranslational processing (16). Although exact positions of the three C-terminal residues (388-390) are unknown because of disorder of these residues, it is certain that conformational change has occurred upon processing, most probably in the C-terminal segment of the L subunit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the C terminus of the L subunit and the N terminus of the S subunit are quite distant from one another with Ser-387 C and Thr-391 N being 36 Å apart. The peptide bond between Gln-390 and Thr-391 is cleaved autocatalytically by posttranslational processing (16). Although exact positions of the three C-terminal residues (388-390) are unknown because of disorder of these residues, it is certain that conformational change has occurred upon processing, most probably in the C-terminal segment of the L subunit.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to highly purify large quantities of soluble enzyme makes E. coli GGT an ideal enzyme to study the general reaction mechanisms of this class of enzyme. Using this system, we established that autocatalytic posttranslational processing occurs in the precursor protein, in which Thr-391 acts as the nucleophile, to produce the large (L) and small (S) subunits (16). We also identified that the O␥ atom of N-terminal Thr-391 of the S subunit acts as the nucleophile in its enzymatic reaction (17).…”
mentioning
confidence: 96%
“…After autocleavage, T381 forms the N-terminus of the small subunit and serves as the catalytic residue in the active site of hGGT1 (6). This intramolecular autocatalytic maturation is essential to the functional activation of the enzyme and is a hallmark of all known GGT orthologs, ranging from bacteria to humans (3,6,24,46,47). The mature extracellular heterodimer is held together by electrostatic interactions and remains tethered to the plasma membrane by a single-pass transmembrane domain (a.a. that is located at the N-terminus of the large subunit (Fig.…”
mentioning
confidence: 99%
“…One unique feature of the Ntnhydrolases is that a single nucleophilic residue is used as the reactive nucleophile for both the autoproteolytic and enzymatic activity (14 -17). The N-terminal nucleophile is Cys in glucosamine-6-phosphate synthase (18) and asparagine synthase (19); Ser in penicillin acylase (20,21); and Thr in glycosylasparaginase (GA) (14,16,22), the proteasome (23), ␥-glutamyltranspeptidase (24), and Taspase1 (25). In addition to these proteolytic enzymes, several other proteins such as hedgehog proteins (26,27), inteins (28), and nucleoporins (29,30) also belong to the Ntn-hydrolase family.…”
mentioning
confidence: 99%